Sustainability in Construction : LEED Green Associate Certification Preparation - Alshareef, Husam A. (McGraw-Hill's AccessEngineeringLibrary., 2023)
This comprehensive guide covers green design and building techniques for the construction industry and contains all the tools you need to prep for certification. Sustainability in Construction: LEED Green Associate Certification Preparation targets the many disciplines of environmentally friendly building, including construction, engineering, architecture, business management, real estate, and marketing. The book features complete explanations of sustainable sites, water efficiency, energy, materials, indoor environmental quality, and much more. You will also get an accurate mock-up LEED Green Associate Exam complete with answers.